Ameliorating effect of Erxian decoction combined with Fructus Schisandrae chinensis (Wu Wei Zi) on menopausal sweating and serum hormone profiles in a rat model. Issue 1 (December 2016) - Wang, Shi; Wu, Fei; Zhang, Yan; Zhang, Liang; Su, Jing; Wong, Hei; Liu, Ai; Cheung, Ho; Ng, Tzi; Tong, Yao; Sze, Stephen
Abstract Background ModifiedErxian decoction (MEXD), i.e., Erxian decoction (EXD) with FructusSchisandrae chinensis (Wu Wei Zi ) added, has been used to alleviate menopausal symptoms. This study aimed to investigate the effects of MEXD on menopausal sweating and serum hormone levels in a rat model of menopause after oral administration of MEXD. Methods Quality control of MEXD was conducted by employing a reversed-phase high performance liquid chromatography column. The three treatment groups received oral administration of MEXD in 0.5% sodium carboxylmethyl cellulose (CMC-Na) at three different doses (5.5, 11, and 22 g/kg body weight) once-daily for 6 consecutive weeks, with 10 animals per group.Huangqijing oral liquor (5 mL/kg) prepared from the roots ofHuang qi (Astragalus membranaceus ) with an antiperspirant effect was used as a positive control. The negative control group received the same volume of vehicle (0.5% CMC-Na). Ten 3-month-old Sprague–Dawley rats were used as a young group for comparison with the treatment groups (12–14 months old rats). Blood was collected from all animals after 3–6 weeks of treatment. At the end of the treatment, the uterine weight, ovarian weight, and body weight were recorded. Serum malondialdehyde contents and superoxide dismutase activities were determined by thiobarbituric acid colorimetric assays and chemoluminescence assays, respectively. Serum levels of estradiol, follicle-stimulating hormone, and luteinizing hormone were measured by radioimmunoassays. Rat foot pad assays were used to determine the antiperspirant activity of MEXD and histological examinations were conducted on plantar sweat glands. Results Treatment with MEXD (11 g/kg) significantly inhibited sweat excretion in the menopause model rats after treatment for 3 (P = 0.0026) and 6 (P < 0.0001) weeks. The decoction markedly decreased the number of secretory cells in plantar sweat glands. In addition, MEXD (11 g/kg) significantly increased the serum estradiol levels (P < 0.001) and superoxide dismutase activities (P = 0.0405). Furthermore, MEXD (11 g/kg) markedly decreased the serum levels of follicle-stimulating hormone (P = 0.001), luteinizing hormone (P = 0.0213), and malondialdehyde (P = 0.01). Conclusion ModifiedErxian decoction significantly inhibited sweat excretion, regulated serum levels of pituitary gonadotropins and estradiol, and exhibited antioxidative effects in a rat model of menopause.